2017
DOI: 10.1364/ol.42.002571
|View full text |Cite
|
Sign up to set email alerts
|

Low-loss Kagome hollow-core fibers operating from the near- to the mid-IR

Abstract: We report the fabrication and characterization of Kagome hollow-core antiresonant fibers, which combine low attenuation (as measured at ∼30  cm bend diameter) with a wide operating bandwidth and high modal purity. Record low attenuation values are reported: 12.3 dB/km, 13.9 dB/km, and 9.6 dB/km in three different fibers optimized for operation at 1 μm, 1.55 μm, and 2.5 μm, respectively. These fibers are excellent candidates for ultra-high power delivery at key laser wavelengths including 1.064 μm and 2.94 μm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Since then, much progress has been made in both understanding the entailed guidance mechanism [2] and in its transmission performance. The latter has been continuously improved since the introduction of hypocycloid core contour (i.e., negative curvature core contour) in 2010, which led, within a short period of time, to several and successive record loss figures in the visible/ near-infrared [3,5,11,16,17]. The most recent one reported presents a loss figure of 7.7 dB/km at 750 nm using tubular amorphous lattice HC-PCF [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, much progress has been made in both understanding the entailed guidance mechanism [2] and in its transmission performance. The latter has been continuously improved since the introduction of hypocycloid core contour (i.e., negative curvature core contour) in 2010, which led, within a short period of time, to several and successive record loss figures in the visible/ near-infrared [3,5,11,16,17]. The most recent one reported presents a loss figure of 7.7 dB/km at 750 nm using tubular amorphous lattice HC-PCF [7].…”
mentioning
confidence: 99%
“…The introduction of hypocycloid core contour was a direct consequence of the IC mechanism where the fiber-core guidance is based on strongly reducing the optical overlap between the guided core mode and the continuum cladding modes. This in turn explains the loss reduction from a decibel per meter (dB/m) level in the first IC guiding HC-PCF, which took the form of a Kagome lattice cladding surrounding a hollow core with a circular [1] or a hexagonal core contour [2], to a tens of dB/km level in hypocycloid core-contour HC-PCF [3,5,11,16,17]. The impact of the corecontour geometry on the fiber confinement loss (CL) was detailed in [5], where it was shown that the larger the negative curvature of the core-contour cups, the lower the CL and fraction of the power overlap one can reach.…”
mentioning
confidence: 99%
“…Based on their guidance mechanism, HC-PCFs are broadly categorised as hollow core photonic bandgap fibers (HC-PBGFs) and hollow core antiresonant/inhibited coupling fibers (HC-ARF). Within the broad HC-ARF category, many different fiber topologies have emerged, such as those with a Kagome cladding (K-HCF) [5][6][7], or a simpler structure with a single ring of touching or non-touching/non-contact tubes as antiresonant elements [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…All authors are with the Optoelectronics Research Centre, University of Southampton, Southampton, SO17 1BJ, UK (e-mail:m.b.syed-they can already compete with HC-PBGFs, albeit with an increased bend loss [6,7]. The main reason behind such dramatic recent improvement has been the realization of the importance of imposing a negative curvature hollow core boundary [5, 8 and 10-12].…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in the attenuation of K-ARFs at a range of wavelengths have recently been reported [8]. The Stokes signal strengths recorded using the K-ARF are compared to results from a similar length HC-PBGF, operating in the same conditions in the same spectral region.…”
Section: Introductionmentioning
confidence: 99%